Public perception of the myth in traditional objects at the Buka Luwur ceremony of the Sunan Kudus tomb - Nikmah, Faridhatun (SHAHIH: Journal of Islamicate Multidisciplinary, 2023)
This study aims to determine the process of the Buka Luwur ceremony of the Holy Sunan Tomb and the public's perception of objects in the Buka Luwur ceremony of the  Sunan Kudus tomb. This uses a qualitative method and describing data descriptively. The results of this study show that the procession of the Buka Luwurceremony of the tomb of Sunan Kudus is crossed on the 1st-10th of Muharam which is the recitation of the night of 1 Suro, the release of luwur, munadharah masail diniyah, Rosul prayers and papat flying, quranickhatamanbilghoib, orphan compensation, distribution of asyura porridge, recitation of qasidah Al-Barzanji, evening recitation of 10 Suro, distribution of brekat copies,  the division of the shadaqahbrekat, the division of the general brekat, and the ceremony of installing the luwur of the Holy Sunan Tomb. In the procession of the Buka Luwur ceremony of the Tomb of Sunan Kudus, there is public belief in objects that are believed to have magical powers, including water used for sharpening or purifying Cinthakakris, used cloth from BukaLuwur, cicada rice, and asyura porridge, teak leaves, and blessing rice. It is believed that the community can bring blessings, facilitate rizki, cure diseases, fertilize plants, predict clothing and food in the coming year, and so on.